Oxford studies in philosophy of religion. Volume 4 - Kvanvig, Jonathan L. (Oxford : Oxford University Press, 2013)
'Oxford Studies in Philosophy of Religion' is an annual volume offering a regular snapshot of state-of-the-art work in this longstanding area of philosophy. Topics covered include secular belief, theories of analogical predication, nominalism and divine aseity, meticulous providence and gratuitous evil, many-one identity and how it relates to the Trinity, atheism and theistic belief, the Epistemology of the Agape struggle, Wittgensteinian Quasi-Fideism, the semantics for blasphemy, and grounding and omniscience.
Description based on online resource; title from home page (viewed on Dec. 14, 2012).
Includes bibliographical references and index.
Keywords: Religion -- Philosophy